Pengaruh Penggunaan Strategi Pembelajaran Team Quiz Terhadap Hasil Belajar Siswa pada Mata Pelajaran IPS Materi Masa Pra Aksara Hindu, Budha dan Islam di Kelas VII MTs Yayasan Pembangun Didikan Islam (YAPDI) Medan - Hermansyah Putra; Nasrul Syakur Chaniago; Fatkhur Rohman (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2025)
Research on the influence of the Team Quiz learning strategy on student learning outcomes aims to describe the learning outcomes of class VII MTS Islamic Education Development Foundation (YAPDI) Medan and describe the influence of the Team Quiz learning model on student learning outcomes. This research uses quantitative research methods. Data collection techniques are observation, interviews, tests and documentation. The aim of this research is to find out whether there is a significant effect of using the Team Quiz learning model on student learning outcomes in the History subject in class VII MTs Islamic Education Development Foundation. Apart from that, looking at the average scores that have been obtained, it is known that students who study using the Team Quiz model have good learning outcomes with scores compared to students who study using the conventional model.